2015
DOI: 10.1101/033175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of deleterious substitutions in crop genomes

Abstract: Populations continually incur new mutations with fitness effects ranging from lethal to adaptive. While the distribution of fitness effects of new mutations is not directly observable, many mutations likely either have no effect on organismal fitness or are deleterious. Historically, it has been hypothesized that a population may carry many mildly deleterious variants as segregating variation, which reduces the mean absolute fitness of the population. Recent advances in sequencing technology and sequence conse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 88 publications
0
58
0
Order By: Relevance
“…Most previous work on genomic prediction, however, focuses exclusively on the statistical properties of models, ignoring potentially useful biological information (but see Edwards et al, [68] for a recent example). Identifying deleterious alleles may prove a useful tool for crop breeding [69], and our results suggest that incorporating additional annotations-in particular information on evolutionary constraint-can provide additional, inexpensive benefits to existing genomic prediction frameworks.…”
Section: Discussionmentioning
confidence: 90%
“…Most previous work on genomic prediction, however, focuses exclusively on the statistical properties of models, ignoring potentially useful biological information (but see Edwards et al, [68] for a recent example). Identifying deleterious alleles may prove a useful tool for crop breeding [69], and our results suggest that incorporating additional annotations-in particular information on evolutionary constraint-can provide additional, inexpensive benefits to existing genomic prediction frameworks.…”
Section: Discussionmentioning
confidence: 90%
“…A similar phenomenon has been reported for domestic horse genomes, where an excess of deleterious mutations is thought to be caused by domestication and inbreeding (Schubert et al., ). Also in crops, deleterious mutations seem to have accumulated in domestic lineages (Kono et al., ; Lu et al., ).…”
Section: The Domestication Bottleneckmentioning
confidence: 99%
“…A different approach is to assess the mutational load in genes known to affect phenotypic traits of interest. In plants, such genes were shown to contain proportionally more deleterious variants (Kono et al., ; Lu et al., ; Mezmouk & Ross‐Ibarra, ). The linkage of deleterious variants to genes under balancing selection could also lead to a local overrepresentation of deleterious variants.…”
Section: Artificial Selection and Mutational Loadmentioning
confidence: 99%
“…In many previous studies, it has been shown that crop plants experienced a strong selection pressure during the domestication process (Gepts, ; Zohary, ; Purugganan and Fuller, ), which often results in the independent appearance of multiple spontaneous adaptive mutations, most of which are base substitutions (Hall, ). The process of increased prevalence (an increase in the number, frequency and/or proportion) of deleterious mutations in domesticated species, has been described as the ‘cost of domestication’ (Kono et al ., ; Moyers et al ., ). An excess of non‐synonymous substitutions was observed in different domesticated germplasm (Liu et al .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the effects of domestication on the genome have been presented as the ‘cost of domestication’ hypothesis. According to this, domesticated species have acquired an increased prevalence (an increase in the number, frequency and/or proportion) in deleterious genetic variants during the process of domestication (Kono et al ., ; Moyers et al ., ). In different crop species (rice, maize, barley, soybean and sunflower), an increased proportion of non‐synonymous mutations in domesticated taxa relative to their wild progenitors has been documented (Mezmouk and Ross‐Ibarra, ; Renaut and Rieseberg, ; Kono et al ., ; Liu et al .…”
Section: Introductionmentioning
confidence: 98%